Neuroendoscopy Current Status and Future Trends - Sgouros, Spyros; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
During the past decade, neuroendoscopy has undergone a variety of technological improvements, and both indications and techniques have been significantly refined. As a result, neuroendoscopy is now used in the treatment of many more patients, enabling the performance of previously unavailable operations with low complication rates and rapid patient recovery. This book presents the distilled experience of world experts in this evolving field. Current applications are explained in detail and likely future developments are identified. Among the topics discussed are the neuroendoscopic management of hydrocephalus, a wide variety of tumors, colloid and suprasellar arachnoid cysts, Chiari malformation, and craniosynostosis; the use of neuroendoscopic techniques in improving altered CSF physiology; and the status of neuroendoscopically assisted neurosurgery. In addition, the available neuroendoscopic instruments are reviewed and the results of international trials and collaborative studies, presented. This book will fully acquaint the reader with the breadth and depth of available neuroendoscopy techniques and their impressive therapeutic potential. It should serve as the reference bok on neuroendoscopy for the next 10 years.
Historical Trends of Neuroendoscopic Surgery -- The Application of Neuroendoscopic Techniques in Improving Altered CSF Physiology -- International Trials and Collaborative Studies in Neuroendoscopy: Progress so far and Future Potentials -- Controversies in the Endoscopic Management of Various Forms of Hydrocephalus -- Current Status and Future Developments of Neuroendoscopical Management of Pituitary Tumours and Craniopharyngiomas -- Current Status and Future Developments of Neuroendoscopically Assisted Neurosurgery -- Neuroendoscopic Instruments and Surgical Technique -- Integrating Endoscopy in the Technological Environment of the Modern Neurosurgical Operating Room -- Endoscopic Management of Hypothalamic Hamartomas -- Neuroendoscopic Management of Ventricular Tumours in Children -- Neuroendoscopic Management of Colloid Cysts -- State of the Art of MR CSF Flow Imaging -- Neuroendoscopic Management of Suprasellar Arachnoid Cysts -- Neuroendoscopic Management of Parenchymal Lesions -- Neuroendoscopic Techniques in the Management of Pineal Tumours -- Controversies in the Management of Middle Fossa Arachnoid Cysts -- Neuroendoscopy in Spinal Pathology: Experience, Latest Trends and Future Developments.-Endoscopy for Craniosynostosis -- Endoscopic Endonasal Repair of CSF Leak -- Man-to-Machine Interface in Neuroendoscopic Equipment.
Keywords: Medicine; Neurosurgery; Orthopedic surgery; Otorhinolaryngology; Medicine & Public Health; Neurosurgery; Surgical Orthopedics; Otorhinolaryngology